Odpowiedzi

2010-04-14T18:59:35+02:00
H2SO3

H2 = I ( *2 = 2)
S = IV
O3 = -II ( *3 = -6)

H2SO4
H2 = I
S = VI
03 = -II

H3PO3
H3 = I
P = III
O3 = -II

H3PO4
H2 = I
P = V
O4 = -II

HNO2
H = I
N = III
O2 = -VI

HNO3
H = I
N = V
O3 = -II
3 3 3
2010-04-14T19:00:26+02:00
H2S03,- 0 minus 2, h- plus 1, s minus 4
H2SO4,- o minus 2, h plus 1 ,s minus 6
H3PO3,, o minus 2, h plus 1 ,p minus 3
H3PO4, o minus 2, h plus 1 ,p minus 5
HNO2, o minus 2, h plus 1 ,n minus 3
HNO3 o minus 2, h plus 1 ,n minus 5
2 1 2
2010-04-14T19:07:29+02:00
H ZAWSZE w kwasach ma I
O za zwyczaj ma -II Ogólne reguły poszukaj w książkach :)
H2SO4
H=I
O= -II
S=
-II *4 = -8
-8 + 2* 1 = -VI

H2SO3
-II *3 = -6
-6 + 2*1 =- 4
S= IV
H=I
0= -II

H3PO3
H=I
0= -II
-II * 3= -6 P
-6 +3 = -III

H3PO4
H-I
O- -II
P = -8+3=V

HNO2
H=I
0= -II
N= -4+1= -III

HNO3
H=1
0=-II
N= -6+1= -V

3 2 3